2011
DOI: 10.1111/j.1447-0756.2011.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum maternal hepcidin levels 3 days after delivery are higher compared to those measured at parturition

Abstract: Factors triggering hepcidin synthesis dominate 3 days after delivery. Studies are needed to assess the contribution of hepcidin to iron homeostasis during the periparturition period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…However, the uniform direction of the results obtained, as confirmed in a subanalysis of women whose blood samples were available during all time points, provide confidence in results obtained. In addition, our findings on gestational serum hepcidin levels were in agreement with previously assessed hepcidin concentration in first, second and third trimester [ 12 ] as were the increased hepcidin levels directly postpartum [ 11 ]. Another limitation is that we were not informed about the use of over-thecounter iron supplements.…”
Section: Discussionsupporting
confidence: 89%
“…However, the uniform direction of the results obtained, as confirmed in a subanalysis of women whose blood samples were available during all time points, provide confidence in results obtained. In addition, our findings on gestational serum hepcidin levels were in agreement with previously assessed hepcidin concentration in first, second and third trimester [ 12 ] as were the increased hepcidin levels directly postpartum [ 11 ]. Another limitation is that we were not informed about the use of over-thecounter iron supplements.…”
Section: Discussionsupporting
confidence: 89%
“…This review reveals a significant paucity of studies assessing hepcidin during pregnancy. Ten human [47,48,49,50,51,52,53,54,55,56] and six animal studies [57,58,59,60,61,62] met the inclusion criteria with findings reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the ten human studies utilized a cross-sectional study design [47,48,49,50,51,52] and four were longitudinal [53,55,56,68]. Sample size for the human studies ranged from 19 [52] to 191 subjects [48].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with prior studies (23,46), high iron demand during lactation has no profound effect on the expression of iron transporters in the mammary gland or liver hepcidin. Indeed, serum hepcidin levels return to normal levels immediately after delivery (15), where intestinal HIF-2α signaling uncouples a repressive effect of hepcidin on intestinal iron absorption. The present work shows that intestinal HIF-2α is not only a critical regulator, but also an essential sensor of maternal iron demand during lactation and essential to maintain adequate levels of iron in breast milk by enhancing the expression of intestinal iron absorption genes.…”
Section: Discussionmentioning
confidence: 99%
“…This is a highly conserved process observed in humans and animal models (12)(13)(14). However, hepcidin levels are restored after parturition or early lactation period during which the maternal iron requirement is still at its peak (15,16). This suggests alternative mechanisms exist during late pregnancy and lactation that allow efficient intestinal iron absorption independent of hepcidin levels.…”
mentioning
confidence: 99%